Leptospira enrichment culture followed by ONT metagenomic sequencing allows better detection of Leptospira presence and diversity in water and soil samples. - Myranda Gorman; Ruijie Xu; Dhani Prakoso; Liliana C M Salvador; Sreekumari Rajeev (Public Library of Science (PLoS), 2022)
Background Leptospirosis, a life-threatening disease in humans and animals, is one of the most widespread global zoonosis. Contaminated soil and water are the major transmission sources in humans and animals. Clusters of disease outbreaks are common during rainy seasons. Methodology/principal findings In this study, to detect the presence of Leptospira, we applied PCR, direct metagenomic sequencing, and enrichment culture followed by PCR and metagenomic sequencing on water and soil samples. Direct sequencing and enrichment cultures followed by PCR or sequencing effectively detected pathogenic and nonpathogenic Leptospira compared to direct PCR and 16S amplification-based metagenomic sequencing in soil or water samples. Among multiple culture media evaluated, Ellinghausen-McCullough-Johnson-Harris (EMJH) media containing antimicrobial agents was superior in recovering and detecting Leptospira from the environmental samples. Our results show that enrichment culture followed by PCR can be used to confirm the presence of pathogenic Leptospira in environmental samples. Additionally, metagenomic sequencing on enrichment cultures effectively detects the abundance and diversity of Leptospira spp. from environmental samples. Conclusions/significance The selection of methodology is critical when testing environmental samples for the presence of Leptospira. Selective enrichment culture improves Leptospira detection efficacy by PCR or metagenomic sequencing and can be used successfully to understand the presence and diversity of pathogenic Leptospira during environmental surveillance.